Birds of paradise - van der Weijde, Erik ([New York] : 4478zine, 2012)
Newspaper - Artist's Description: Birds of Paradise is a project made especially for Brooklyn Shelf Life, commissioned by Brooklyn Academy of Music. This tabloid sized paper shows a cut-and-paste re-interpretation of a book on War Tanks, based on a sketched version made in Japan during a long night.
boek
Keywords: van der Weijde, Erik